CGIAR and the Linux foundation partner to unlock agricultural field data at global scale - CGIAR Initiative on Digital Innovation (CGIAR System Organization, 2022)
Washington, DC/Nairobi, Kenya, September 14, 2022 – CGIAR and the Linux Foundation have formed a research partnership to develop a standard way of sharing data about agricultural fields at scale, which could deliver global benefits, including for the estimated 500 million smallholder farmers that produce about a third of the world’s food.